2017
DOI: 10.1038/s41598-017-14008-5
|View full text |Cite|
|
Sign up to set email alerts
|

Computational Analysis of the Molecular Mechanism of RamR Mutations Contributing to Antimicrobial Resistance in Salmonella enterica

Abstract: Antimicrobial resistance (AMR) in pathogenic microorganisms with multidrug resistance (MDR) constitutes a severe threat to human health. A major causative mechanism of AMR is mediated through the multidrug efflux pump (MEP). The resistance-nodulation-division superfamily (RND family) of Gram-negative bacteria is usually the major cause of MDR in clinical studies. In Salmonella enterica, the RND pump is translated from the acrAB gene, which is regulated by the activator RamA. Many MEP-caused AMR strains have hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Certain mutations in ramR, such as those detected here (i. e. Y59H, M84I, E160D), affect the DNA binding affinity of RamR and reduce the repression of the ramA gene. This disruption leads to overexpression of ramA, which activates the major efflux-mediated AMR mechanism in Gram-negative bacteria: the acrAB-tolC RND multidrug efflux pump [53,54]. This feature is a broad-spectrum efflux system that confers resistance to unrelated antibiotic classes such as tetracyclines, quinolones, phenicols and beta-lactams [55].…”
Section: Discussionmentioning
confidence: 99%
“…Certain mutations in ramR, such as those detected here (i. e. Y59H, M84I, E160D), affect the DNA binding affinity of RamR and reduce the repression of the ramA gene. This disruption leads to overexpression of ramA, which activates the major efflux-mediated AMR mechanism in Gram-negative bacteria: the acrAB-tolC RND multidrug efflux pump [53,54]. This feature is a broad-spectrum efflux system that confers resistance to unrelated antibiotic classes such as tetracyclines, quinolones, phenicols and beta-lactams [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, computational analyses have indicated that mutations in the dimerization domain of RamR can lead to a reduction in its DNA binding affinity in Salmonella spp. 55 . In our study, mutations in RamR were detected in both DNA binding and dimerization domains but mostly were point mutations that occurred outside hotspot regions.…”
Section: Discussionmentioning
confidence: 99%
“…RamR is the repressor of RamA and several mutations were identified in its dimerization domain, resulting in a decrease of DNA-binding affinity on the promoter of ramA in Salmonella [ 78 ]. It recognizes multiple chemicals such as bile components, crystal violet, ethidium bromide, rhodamine G, and the resulting association reduces its proper affinity for DNA target sites [ 79 ].…”
Section: Regulators Type 1—helix-turn-helix (Hth) Family Regulatormentioning
confidence: 99%